Jonathan Franzen’s The Corrections : ethics of complexity - Hosseini, Sayyede Maryam; Pirnajmuddin, Hossein; Abbasi, Pyeaam (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper examines Jonathan Franzen’s particular version of realism in The Corrections in terms of a number of seminal concerns including the discourse of ethics, cognition, and social minds. As a (post-)postmodern writer, Jonathan Franzen conflates contemporaneity, timelessness, placelessness and nonbelonging of his time with naturalism’s determinism and realism’s detailed description to offer a new version of realism called neorealism or, in his own words, tragic realism. Central to this new version of realistic fiction is the illustration of a complicated network of community, place, and the individual. The Corrections, in this regard, is a novel whose humanistic aspects show Franzen’s faith in the possibility of certain kinds of ‘corrections’ and hence changes in the ethical and moral conditions of the characters. Franzen’s tragic realism, despite showing the tragic and deterministic aspects of life, makes his readers and characters rethink what has long been taken for granted about familial, communal, and generational relationships. Thus it rekindles hopes in the possibility of mutual ethical (re)cognition of the other attainable via retrospective questioning made possible in the individuals’ oscillations between certainty and doubt (i.e. epistemic imbalance). Franzen achieves these effects through displaying the complexity of the ordinary aspects of the lives of ordinary people to revive faith in ethical, humanistic and even empathic responsibility, through describing the characters’ appreciation of the ethics of complexity. These relations often involve accepting or tolerating human flaws as the juxtaposition of tragic and realism suggests.